2012
DOI: 10.1002/ibd.21801
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography enterography findings correlate with tissue inflammation, not fibrosis in resected small bowel Crohnʼs disease

Abstract: CTE findings of mesenteric hypervascularity, mucosal hyperenhancement, and mesenteric fat stranding predict tissue inflammation. However, small bowel stricture without CTE findings of inflammation does not predict the presence of tissue fibrosis. Therefore, caution should be used when using CTE criteria to predict the presence of scar tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 174 publications
(130 citation statements)
references
References 30 publications
3
126
1
Order By: Relevance
“…Strictures in Crohn's disease can be inflammatory, fibrotic, or (most commonly) a combination of both. Ongoing efforts aim to validate approaches to addressing the relative contributions of active inflammation and fibrosis in Crohn's strictures, which is not possible at CT enterography [40]. If we can accurately make this distinction, gastroenterologists can more effectively triage patients to potent medical therapy vs. surgical intervention and avoid the morbidity inherent in misclassification in either direction (Fig.…”
Section: Mre Findings Used For Diagnosing Crohn's Diseasementioning
confidence: 99%
“…Strictures in Crohn's disease can be inflammatory, fibrotic, or (most commonly) a combination of both. Ongoing efforts aim to validate approaches to addressing the relative contributions of active inflammation and fibrosis in Crohn's strictures, which is not possible at CT enterography [40]. If we can accurately make this distinction, gastroenterologists can more effectively triage patients to potent medical therapy vs. surgical intervention and avoid the morbidity inherent in misclassification in either direction (Fig.…”
Section: Mre Findings Used For Diagnosing Crohn's Diseasementioning
confidence: 99%
“…Recent investigations have shown that contrast-enhanced US with microbubble contrast agents can be used to objectively assess disease activity in adults with small bowel Crohn disease (17,18). rowing have an active inflammatory component (Fig 9), although underlying fibrosis can also be present (19). Strictures without increased blood flow at Doppler US are commonly fibrotic and are less likely to respond to medical therapy.…”
Section: Hyperemiamentioning
confidence: 99%
“…These signs of active inflammation are clinically relevant because they usually indicate the potential for response to medical therapy, which can relieve the obstruction by reducing the inflammation [30]. Diagnosing a fibrotic stricture is more challenging as the absence of imaging signs of active inflammation is not diagnostic of fibrosis [31].…”
Section: Single Transition Zonementioning
confidence: 99%